The Attorney-General, politics and logistics – a fork in the road?. (September 2022) - Hand, James
Abstract: The appointment of recent Attorney-Generals for England and Wales has occasioned much comment about their experience. This paper considers whether, following the transmogrification of the Lord Chancellorship over a decade ago, the backgrounds and activities of recent leaders of the Attorney-General's Office suggest the time is now right for similar changes to the Law Officers' roles. In doing so, it presents a range of original data on aspects of the role and on characteristics of Attorney-Generals, which suggests that unless self-restraint is exercised (by the Prime Minister and the post-holders) we may ineluctably be on the path to reform.